Analisa Implementasi Manajemen Proyek pada Pengembangan Karung Goni Menjadi Tas yang Bermanfaat - Ewaldo, Davin; Setiawan, Michael; Angesty, Viviana; Firdiansyah, Ronny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
TasGon is a product made from jute sack waste which is then processed into a useful product. In this project the burlap sack is processed into a bag called TasGon. This TasGon has many benefits, namely it can reduce the waste of burlap sacks that are wasted everywhere. In this study the authors used qualitative and descriptive research methods. This research is continued by analyzing project management, namely Project Integration, Project Scope Management, Project Time Management, Project Cost Management, Project Quality Management, Project Human Resource Management, Project Communication Management, Project Risk Management, Project Procurement Management, Project Stakeholder Management. The results of this study indicate that TasGoni has many benefits that can be felt by many people. Therefore the project undertaken must be in accordance with the quality of the product produced. Keywords: Project Management, Gunny Sack, Waste